The COMET Initiative database: progress and activities update (2015). Issue 1 (December 2017) - Gargon, E.; Williamson, P.; Altman, D.; Blazeby, J.; Tunis, S.; Clarke, M.
Abstract This letter describes the substantial activity on the Core Outcome Measure in Effectiveness Trials (COMET) website in 2015, updating our earlier progress reports for the period from the launch of the COMET website and database in August 2011 to December 2014. As in previous years, 2015 saw further increases in the annual number of visits to the website, the number of pages viewed and the number of searches undertaken. The sustained growth in use of the website and database suggests that COMET is continuing to gain interest and prominence, and that the resources are useful to people interested in the development of core outcome sets.